Genetic variants in the regulatory T cell-related pathway and colorectal cancer prognosis - Neumeyer, Sonja; Hua, Xinwei; Seibold, Petra Beate; Jansen, Lina; Benner, Axel; Burwinkel, Barbara; Halama, Niels; Berndt, Sonja I.; Phipps, Amanda I.; Sakoda, Lori C.; Schoen, Robert E.; Slattery, Martha L.; et al. (Cancer epidemiology, biomarkers & prevention, 2020)
Background: High numbers of lymphocytes in tumor tissue, including T regulatory cells (Treg), have been associated with better colorectal cancer survival. Tregs, a subset of CD4+ T lymphocytes, are mediators of immunosuppression in cancer, and therefore variants in genes related to Treg differentiation and function could be associated with colorectal cancer prognosis. - Methods: In a prospective German cohort of 3,593 colorectal cancer patients, we assessed the association of 771 single-nucleotide polymorphisms (SNP) in 58 Treg-related genes with overall and colorectal cancer-specific survival using Cox regression models. Effect modification by microsatellite instability (MSI) status was also investigated because tumors with MSI show greater lymphocytic infiltration and have been associated with better prognosis. Replication of significant results was attempted in 2,047 colorectal cancer patients of the International Survival Analysis in Colorectal Cancer Consortium (ISACC). - Results: A significant association of the TGFBR3 SNP rs7524066 with more favorable colorectal cancer-specific survival [hazard ratio (HR) per minor allele: 0.83; 95% confidence interval (CI), 0.74-0.94; P value: 0.0033] was replicated in ISACC (HR: 0.82; 95% CI, 0.68-0.98; P value: 0.03). Suggestive evidence for association was found with two IL7 SNPs, rs16906568 and rs7845577. Thirteen SNPs with differential associations with overall survival according to MSI in the discovery analysis were not confirmed. - Conclusions: Common genetic variation in the Treg pathway implicating genes such as TGFBR3 and IL7 was shown to be associated with prognosis of colorectal cancer patients. - Impact: The implicated genes warrant further investigation.
Gesehen am 15.02.2021